The prevalence of nicotine dependence in psychiatric outpatients - Yıldız, Mustafa; Özcan, M. Erkan (Journal of Dependence, 2000)
Object: The aim of this study was to determine the prevalence of nicotine dependence in psychiatric outpatients. Method: We examined 304 consecutive psychiatric outpatients diagnosed by clinical interview according to DSM-IV. Results: The prevalence of nicotine dependence was 29.3% in all of the patients, 70.6% in patients with bipolar disorders, 44.1% in patients with psychotic disorders, 25.8% in patients with anxiety disorders, 25.3% in patients with depressive disorders, 30.0% in patients with sexual dysfunctions, 25.0% in patients with adjustment disorders, and 21.2% in patients with somatoform disorders. 60.7% of patients with nicotine dependence had been dependent before the onset of psychiatric disorder. Patients with psychotic disorders had higher number of average daily cigarette consumption than other patients. Discussion: The nicotine dependence may be directly related to the psychopathology with respect to its severity and duration.
Keywords: Anxiety disorder; depressive disorder; bipolar disorder; psychotic disorder; somatoform disorder; adjustment disorder; sexual dysfunctions; nicotin dependence; prevalence